2013
DOI: 10.1111/bcp.12139
|View full text |Cite
|
Sign up to set email alerts
|

The cancer therapeutic potential of Chk1 inhibitors: how mechanistic studies impact on clinical trial design

Abstract: Many anticancer agents damage DNA and activate cell cycle checkpoints that permit time for the cells to repair their DNA and recover. These checkpoints have undergone intense investigation as potential therapeutic targets and Chk1 inhibitors have emerged as promising novel therapeutic agents. Chk1 was initially recognized as a regulator of the G2/M checkpoint, but has since been demonstrated to have additional roles in replication fork stability, replication origin firing and homologous recombination. Inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
108
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 79 publications
4
108
0
Order By: Relevance
“…damaging agents (8). The key role that CHK1 plays in the rapid activation of the S and G 2 -M checkpoints is due to the tight integration of CHK1 into normal DNA replication and DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…damaging agents (8). The key role that CHK1 plays in the rapid activation of the S and G 2 -M checkpoints is due to the tight integration of CHK1 into normal DNA replication and DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death brought about by this combination of replication failure, DSB generation, and loss of DNA damage checkpoints has been called replication catastrophe (13). A number of CHK1 inhibitors have entered clinic trials, primarily in combination with DNA-damaging agents (7,8). LY2606368 was developed as a second-generation CHK1 inhibitor to have increased potency in vivo and is being assessed clinically both as a single agent (NCT01115790) as well as in combination with cytotoxic and targeted agents (NCT02124148).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CHK1 inhibitors have not yet been combined with radiotherapy in clinical trials, possibly due to inadequate selectivity and/or unexpected toxicities observed with earlier compounds (25,26). The CHK1 inhibitor CCT244747 is a highly selective, potent, orally active ATP-competitive CHK1 inhibitor previously shown to enhance the activity of several genotoxic agents, including ionizing radiation (13).…”
Section: Discussionmentioning
confidence: 99%
“…16 Chk1 is an essential kinase in governing cell cycle G 1 /S, S, and G 2 /M phase checkpoints and determining cellular responses to DNA damage. [22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression.…”
Section: Discussionmentioning
confidence: 99%